PORTFOLIO DIVERSIFICATION STRATEGY AND ITS INFLUENCE ON INVESTMENT RISK AND RETURN IN THE CAPITAL MARKET - Munizu, Musran; Mulyati, Sri; Zikirullaeva, Nilufar (Multifinance, 2024)
The objective of this study is to examine the impact of diversification methods on the risk and return of investments in the capital market. The employed research methodology is qualitative research, which is a strategy utilized to gain a comprehensive understanding of social phenomena. This research methodology involves conducting a comprehensive examination and analysis of relevant written sources, such as books, journals, articles, and documents, to gather information pertaining to the specific topic or title under investigation. The research findings indicate that the diversity strategy portfolio plays a key role in risk management and has an impact on investment returns in the capital market. The diversity of the portfolio is successful in reducing risk, particularly through the distribution of funds across different assets and sectors. This subject is substantiated by empirical evidence and case studies, which demonstrate that a diversified portfolio has the capability to safeguard investments from substantial swings in the market. In the face of capital market unpredictability, diversifying a portfolio is a method that cannot be avoided. By gaining a profound comprehension of risk variables, market dangers, and the economic and political influences on the market, investors can create an ideal portfolio that aligns with their investing objectives. This approach ensures more consistency and measurability over the long term.